Economic analysis of dengue prevention and case management in the Maldives. - Mathieu Bangert; Aishath Thimna Latheef; Shushil Dev Pant; Ibrahim Nishan Ahmed; Sana Saleem; Fathimath Nazla Rafeeq; Moomina Abdulla; Fathimath Shamah; Ahmed Jamsheed Mohamed; Christopher Fitzpatrick; Raman Velayudhan; Donald S Shepard (Public Library of Science (PLoS), 2018)
As tourism is the mainstay of the Maldives' economy, this country recognizes the importance of controlling mosquito-borne diseases in an environmentally responsible manner. This study sought to estimate the economic costs of dengue in this Small Island Developing State of 417,492 residents. The authors reviewed relevant available documents on dengue epidemiology and conducted site visits and interviews with public health offices, health centers, referral hospitals, health insurers, and drug distribution organizations. An average of 1,543 symptomatic dengue cases was reported annually from 2011 through 2016. Intensive waste and water management on a resort island cost $1.60 per occupied room night. Local vector control programs on inhabited islands cost $35.93 for waste collection and $7.89 for household visits by community health workers per person per year. Ambulatory care for a dengue episode cost $49.87 at a health center, while inpatient episodes averaged $127.74 at a health center, $1,164.78 at a regional hospital, and $1,655.50 at a tertiary referral hospital. Overall, the cost of dengue illness in the Maldives in 2015 was $2,495,747 (0.06% of gross national income, GNI, or $6.10 per resident) plus $1,338,141 (0.03% of GNI or $3.27 per resident) for dengue surveillance. With tourism generating annual income of $898 and tax revenues of $119 per resident, results of an international analysis suggest that the risk of dengue lowers the country's gross annual income by $110 per resident (95% confidence interval $50 to $160) and its annual tax receipts by $14 per resident (95% confidence interval $7 to $22). Many innovative vector control efforts are affordable and could decrease future costs of dengue illness in the Maldives.